JAK2V617F-positive clonal hematopoiesis of indeterminate potential in pregnant women - I. A. Olkhovskiy; J. G. Garber; A. S. Gorbenko; M. A. Stolyar; O. M. Miller; E. S. Kostina; Yu. Yu. Komarovskiy; V. V. Potilitsina (Акушерство, гинекология и репродукция)
Aim: to assess the prevalence of V617F somatic mutation of the JAK2 gene in pregnant women.Materials and methods. This non-interventional study was performed in the framework of routine clinical practice and included 1532 samples of venous blood from pregnant women who applied for medical assistance at Krasnoyarsk Regional Clinical Center for Maternal and Child Welfare. We used blood samples left after all routine laboratory tests had been done. These leftovers were pooled in the way that ensured an equal ratio of nucleated cells. Each pool contained 7 separate blood samples. The unused samples that remained after the pooling were frozen and stored at –20°C until the end of entire testing procedure. The V617F JAK2 mutation was detected by the real-time allele-specific polymerase chain reaction test.Results. Among the examined pregnant women, 6 (0.4 %) were identified as carriers of V617F JAK2 mutation. Three women with this mutation suffered from infertility for 4, 5, and 10 years; two of them had repeated miscarriages in the first trimester of pregnancy. The 6 women – carriers of this mutations had no concomitant genetic polymorphisms typical of thrombophilia (factors FII, FV), and no abnormal coagulation characteristics. Analysis of their medical records showed that in the past, two of these women had gestational hypertension, one developed a clinical picture of preeclampsia, and another one (with the maximum presence of the mutant allele) had a history of acute lymphoblastic leukemia followed by stable remission.Conclusion. The routine laboratory detection of the V617F JAK2 mutation can facilitate timely identification of the increased risk of pregnancy pathology, as well as timely diagnosis of hematological cancer.